Manfaat Discharge Planning pada Pasien CVA Infark : A Systematic Review - Fetreo Negeo Putra; Nursalam Nursalam; Aang Kunaifi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Background: Discharge planning is a systematic process and pilot of various case that needs continous trearment, for example is CVA infarct. Objective: To find out the function of discharge planning on CVA infarct patient. Method: The database used in this study were Scopus, SAGE and Pubmed were limited to the last 6 years of publication from 2014 to 2020, full-text articles and in English. The keyword used were "discharge planning" AND "CVA infarct” AND “Nursing". This systematic review used 10 articles that fit the inclusion criteria. Results: Benefit from discharge planning for patient with CVA infarct is to identified and assesment level of physical capability patient with CVA infarct, to make sure that patient with CVA infarct ready continous treatment in home, determine rehabilitatif treatment that patient CVA infarct needed in home and decrease statistic readmision of CVA infarct case. Conclusion: Discharge planning have many benefits for patient with CVA infact for rehabilitation after hospitalization and to decrease the number of readmition. Keywords: discharge planning; CVA infarct; nursing ABSTRAK Latar belakang: Perencanaan pulang atau discharge planning merupakan proses sistematis dan panduan pada berbagai kasus penyakit yang membutuhkan perawatan lanjutan diantaranya adalah penyakit CVA infark.. Tujuan: Untuk mengetahui manfaat discharge planning terhadap penyakit CVA infark. Metode: Database yang digunakan dalam penelitian ini adalah Scopus, SAGE dan Pubmed terbatas untuk publikasi 6 tahun terakhir dari 2014 hingga 2020, full text article dan berbahasa Inggris. Kata kunci yang digunakan adalah “Discharge Planning” AND “CVA Infarct” AND “Nursing”. Systematic review ini menggunakan 10 artikel yang sesuai dengan kriteria inklusi. Hasil: Manfaat discharge planning bagi pasien CVA infark adalah untuk mengidentifikasi dan mengkaji tingkat kemampuan fisik dari pasien cva infark, memastikan pasien cva infark siap untuk melanjutkan perawatan di rumah, menentukan tindakan rehabilitatif yang diperlukan pasien CVA infark ketika di rumah dan mengurangi angka terjadinya readmisi pada pasien CVA infark. Kesimpulan: Discharge planning memiliki banyak manfaat bagi pasien CVA infark untuk menjalani rehabilitasi di rumah dan menurunkan angka terjadinya readmisi. Kata kunci: perencanaan pulang; CVA infark; perawat